Diversité Et Importance Socio-Economique Des Espèces Fruitières Sauvages Comestibles En Zone Kasa (Sud-Ouest Du Sénégal) - Yves Djihounouck; Doudou Diop; Sara Danièle Dieng; Seyni Sane; César Bassène; Mame Samba Mbaye; Kandioura Noba (European Scientific Journal, ESJ, 2018)
Wild fruit species provide local people with subsistence products and cash income. In addition to their food value, different used organs can, eventually, compromise the availability of these resources. This study aims to identify edible woody species in Kasa Zone and to analyze their socioeconomic importance. An ethnobotanical survey was conducted with 82 informants. Data collected were analyzed using Epi Info software and uses of species were classified into six categories. A Factorial Correspondence Analysis (FCA) highlighted species-organ relationships. Frequency of citations, fidelity index, selling price were used to show the socio-economic importance of the species. Results identified 62 edible species belonging to 31 families and 54 genera. These species were dominated by Annonaceae, Apocynaceae and generic diversity was more pronounced among Anacardiaceae. Identified species were mainly used for food (53%), energy (16%), technology (12%) and medicinal purposes (12%). The FCA showed three organ-use groups with a strong correlation between fruit and root on the one hand and leaf, bark and wood on the other. The study also identified 16 commercialized species. The fruit was the main organ consumed and marketed. The highest number of organs commercialized were recorded for Elaeis guineensis (4 organs) and Borassus aethiopium (3). These products, often collected and sold by women and children, came from villages and transited to markets through the "bana bana". Their prices depended on the locality isolation and the production period. These results open up perspectives for better management of the supply and commercialization of these forest resources.